2016
DOI: 10.1093/ijnp/pyw061
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression Pattern of Clock Genes in a Rat Model of Depression

Abstract: Background:Abnormalities in circadian rhythms may be causal factors in development of major depressive disorder. The biology underlying a causal relationship between circadian rhythm disturbances and depression is slowly being unraveled. Although there is no direct evidence of dysregulation of clock gene expression in depressive patients, many studies have reported single-nucleotide polymorphisms in clock genes in these patients.Methods:In the present study we investigated whether a depression-like state in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 67 publications
5
51
1
Order By: Relevance
“…Some drugs cannot induce antidepressant effects in animal models of depression even though they have antidepressant effects in normal animals [5253]. Patients with depression and animal models of depression sometimes show disturbances in circadian system functionality [678545556]. Chronopharmacological profiles of antidepressant activity in depressive-like animals could be different from those in normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…Some drugs cannot induce antidepressant effects in animal models of depression even though they have antidepressant effects in normal animals [5253]. Patients with depression and animal models of depression sometimes show disturbances in circadian system functionality [678545556]. Chronopharmacological profiles of antidepressant activity in depressive-like animals could be different from those in normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 2-10% of the genes in the mammalian genome are controlled by clock genes, and these are known as clock-control genes (CCGs) (13)(14)(15). Aberrant expression of clock genes can regulate downstream clock-control genes and cause various diseases, such as cancer, endocrine diseases, cardiovascular illnesses, and depression (3,6,(16)(17)(18). The International Agency for Research on Cancer have identified that the carcinogenesis of aberrant expression of clock genes is equal to that of diesel engine exhaust gas, inorganic lead compounds, and human papilloma virus (19).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we predict that that stress induced pathophysiological firing in the loop consisting of the LHb, DRN and SCN (LHb®DRN®SCN®LHb) may be responsible for changes in daily rhythms associated with mood disorders. Stress and the circadian system exhibit 2way interaction where for example clock proteins CRY 1/2 increase the responsiveness of the HPA-axis (20) while stress-induced increase in glucocorticoids leads to altered clock gene expression in the SCN and regions associated with regulation of mood(21), (22). Stress induces increased firing in the LHb has been shown to activate HPA-axis causing elevated corticosterone release(23).…”
Section: Discussionmentioning
confidence: 99%